Origin of orthogonality of strain-promoted click reactions - Wagner, Johannes Andreas; Mercadante, Davide; Nikić-Spiegel, Ivana; Lemke, Edward A.; Gräter, Frauke (Chemistry - a European journal, 2015)
Abstract Site-specific labeling of biomolecules is rapidly advancing due to the discovery of novel mutually orthogonal reactions. Quantum chemistry studies have also increased our understanding of their relative rates, although these have until now been based on highly simplified reactants. Here we examine a set of strain-promoted click-type cycloaddition reactions of n-propyl azide, 3-benzyl tetrazine and 3-benzyl-6-methyl tetrazine with cyclooctenes/ynes, in which we aim to address all relevant structural details of the reactants. Our calculations have included the obligatory handles used to attach the label and biomolecule as these can critically influence the stereochemistry and electron demand of the reaction. We systematically computed orbital gaps, activation and distortion energies using density functional theory and determined experimental rates for validation. Our results challenge the current paradigm of the inverse electron demand for this class of reactions. We found that the ubiquitous handles, when next to the triple bond of cyclooctynes, can switch the Diels?Alder type ligations to normal electron demand, a class we term as SPINEDAC reactions. Electron donating substituents on tetrazine can enhance normal demand but also increase distortion penalties. The presence and isomeric configuration of handles thus determine the reaction speed and regioselectivity. Our findings can be directly utilized in engineering genuine cycloaddition click chemistries for biological labeling.